Pelatihan pemanfaatan teknologi sebagai media pendukung pembelajaran untuk guru di Kecamatan Sembalun - Baiq Andriska Candra Permana; Hariman Bahtiar; Aswian Editri Sutriandi; Muhammad Djamaluddin; Suhartini Suhartini (Universitas Hamzanwadi, 2021)
The involvement of lecturers, students, and teaching staff is an integral form of the Tri Dharma of higher education. Education has a crucial role and is the primary key to producing quality human resources. In the current practice of teaching and learning activities, many teachers have not used media or technology in teaching. Therefore, it is necessary to increase teacher competence through Community Service Activities to adapt to the industrial era 4.0, which is more likely to use technology in various fields of life, one of which is the world of education. PKM activities were carried out for six villages in Sembalun District to equalize the competence of teachers in the village so that they were equal to teachers in the city in presenting technology-based learning media. This interactive learning media creation training produced enjoyable visual and graphic-based learning to become more exciting and not dull. With the implementation of this activity, teachers have more competence in using technology and have succeeded in building their learning media. Apart from that, the creativity of the teacher increases with this activity